Metallic Interface Induced Ionic Redistribution within Amorphous MoO3 Films. Issue 23 (14th July 2022) - Paparoni, Francesco; Mijiti, Yimin; Kazim, Shafaq; Minicucci, Marco; Pinto, Nicola; D'Elia, Alessandro; Macis, Salvatore; Kim, Changyoung; Huh, Soonsang; Gunnella, Roberto; Marcelli, Augusto; DiCicco, Andrea; et al.
Abstract: The phase evolution and ionic redistribution in amorphous MoO3 films, deposited on metallic aluminium (Al) and copper (Cu) substrates and subjected to distinct thermal treatments, are systematically investigated in this work. It is shown that the metallic interface significantly modifies the formation and dynamics of oxygen vacancies within the resulted structure, reducing the oxygen content of the MoO3 up to x < 2.94. The concentration of the oxygen vacancies can also be extended to the bulk via thermal treatment up to 400 °C. It is demonstrated that the MoO3 structure on metallic substrates is affected either by the diffusion of the metallic atoms inserted from the interface, which results in a formation of the meta‐stable alloy phases in case of Cu, or by the introduction of the oxygen vacancies into the crystalline matrix in case of Al. The oxygen vacancy density in the MoO3 films with a metallic interface can be tuned via optimal choice of the metal and treatment parameters such as temperature and oxygen partial pressure. Furthermore, the intrinsic defects present in the amorphous structure enhance the ionic mobility and diffusion of the metallic ions inside the crystalline structure. Abstract : The ionic redistribution within the amorphous MoO3 films induced by the metallic junction is investigated. The metal interface significantly enhances the redistribution of the oxygen and metallic ions and formation of the oxygen vacancies within the amorphous film. The vacancy formation can be extended to the bulk via optimal thermal treatment parameters.